Possession of Livelihood Assets in Rural Households: An Economic Analysis - Punia, Anusha; Kaushik, Sushma (Indian Journal of Extension Education, 2018)
Agriculture is the principal source of food and livelihood in India. Demographically it is the broadest economic sector and plays a significant role in the overall socio-economic fabric of India. The study was conducted in two districts of Rohtak division namely Sonipat and Karnal by random selection and by selecting one block from each selected district and two villages from each of the selected block at random. From the selected four villages a sample of 300 respondents i.e. 75 small and marginal farm families from each village was drawn at random. Results of the study in physical capital revealed that cent per cent of farm families had their own house, majority (70.0%) of the farm families had high material possession, 85.3 per cent of families were having more than 2.5-5 acre of land. Regarding financial capital, majority of the farm families (82.0%) saved their money in the form of fixed deposit, 63.3 per cent of the farm families had medium agricultural assets. About economic security, 45.0 per cent of families were having annual income ranging between Rs. 3,00,001- 4 lakh, majority (61.3%) of farm families had residential property of worth upto Rs. 3 lakh and 24.6 per cent of families were somewhat dissatisfied with their current financial condition.
Keywords: Agriculture; capital; families; livelihood